The trade-off between inflation and unemployment in an 'MMT world': an open-economy perspective - Emilio Carnevali; Matteo Deleidi (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
This paper is focused on modern monetary theory's (MMT) treatment of inflation from an open-economy perspective. It analyses how the inflation process is explained within the MMT framework and provides empirical evidence in support of this vision. However, it also makes use of a stock-flow consistent open-economy model to underline some limits of the theory when it is applied in the context of a non-US (relatively) open economy with a flexible exchange-rate regime. The model challenges the contention made by MMT-ers that measures such as the job guarantee programme can achieve full employment without facing an inflation-unemployment trade-off.
Keywords: E51; E120; F410; 330; central banking; post-Keynesian; open-economy model